Preparation and Characterization of Stealth Archaeosomes Based on a Synthetic PEGylated Archaeal Tetraether Lipid - Barbeau, Julie (Hindawi Publishing Corporation, 2011)
The present studies were focused on the formation and characterization of sterically stabilized archaeosomes made from a synthetic PEGylated archaeal lipid. In a first step, a synthetic archaeal tetraether bipolar lipid was functionalized with a poly(ethylene glycol), PEG, and (PEG(45)-Tetraether) with the aim of coating the archaeosome surface with a sterically stabilizing hydrophilic polymer. In a second step, Egg-PC/PEG(45)-Tetraether (90/10 wt%) archaeosomes were prepared, and their physicochemical characteristics were determined by dynamic light scattering (size, polydispersity), cryo-TEM (morphology), and by high-performance thin layer chromatography (lipid composition), in comparison with standard Egg-PC/PEG(45)-DSPE formulations. Further, a fluorescent dye, the carboxyfluorescein, was encapsulated into the prepared archaeosomes in order to evaluate the potential of such nanostructures as drug carriers. Release studies have shown that the stability of Egg-PC/PEG(45)-Tetraether-based archaeosomes is significantly higher at 37°C than the one of Egg-PC/PEG(45)-DSPE-based liposomes, as evidenced by the slower release of the dye encapsulated into PEGylated archaeosomes. This enhanced stability could be related to the membrane spanning properties of the archaeal bipolar lipid as already described with natural or synthetic tetraether lipids.